They Called It Peace: Worlds of Imperial Violence - Martino Tognocchi (Athena, 2025)
Lauren Benton’s new book, They Called It Peace, offers a comprehensive view of the various forms of violence that European empires deployed overseas from the early modern period to the 19th century. These forms of violence—ranging from household abuses and slavery to deliberate killings and mass exterminations—soon became routine mechanisms for maintaining colonial rule. As the author convincingly demonstrates through a solid theoretical framework and rich historical evidence, small wars were far from marginal, despite being represented as such by Europeans. Rather, they had global implications for legal, political, and cultural imaginaries, resonating to this day. This review aims to highlight the book’s important contributions to both the history of international law and global history.